2012
DOI: 10.3382/ps.2011-01899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monochromatic light stimuli during embryogenesis on muscular growth, chemical composition, and meat quality of breast muscle in male broilers

Abstract: This study was conducted to evaluate the effect of monochromatic light stimuli during embryogenesis on breast muscle growth, chemical composition, and meat quality of male broilers. Fertile broiler eggs (Arbor Acres; n = 1,320) were preweighed and randomly assigned to 1 of 3 treatment groups in 3 modified incubators: 1) control group (in dark condition), 2) monochromatic green light group (560 nm), and 3) monochromatic blue light group (480 nm). The monochromatic lighting systems sourced from light-emitting di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 22 publications
2
54
3
1
Order By: Relevance
“…Green light exposure during incubation has also been observed to down regulate the green and red opsins, whereas red light enhances their expression (Rozenboim et al, 2013). Green light exposure during incubation has also been shown to improve feed conversion ratio (FCR) post-hatch in broilers (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Green light exposure during incubation has also been observed to down regulate the green and red opsins, whereas red light enhances their expression (Rozenboim et al, 2013). Green light exposure during incubation has also been shown to improve feed conversion ratio (FCR) post-hatch in broilers (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies showed that white light provided by incandescent lamps stimuli during incubation elevated egg core temperature, which further accelerated embryo development and shortened hatching time (Shutze et al, 1962;Siegel et al, 1969). However, both low-power LED lamps and microcomputer automatic temperature control incubator can adjust the core temperature to maintaining a set value (37.8±0.1°C), which also offers an explanation why no significant difference in hatching time was found in our previous study (Zhang et al, 2012).…”
Section: 2014)mentioning
confidence: 44%
“…During this stage, embryo survival rates improved when concentrations of embryonic thyroid hormones increased (Christensen and Davis, 2004). In the current study, both plasma T4 and T3 levels in embryo chicks were not affected by continuous green light stimuli during incubation, which may be linked to the absence of significant difference in death of the embryos and hatchability between the green light and control (Zhang et al, 2012;2014). In addition, previous studies showed that white light provided by incandescent lamps stimuli during incubation elevated egg core temperature, which further accelerated embryo development and shortened hatching time (Shutze et al, 1962;Siegel et al, 1969).…”
Section: 2014)mentioning
confidence: 62%
See 2 more Smart Citations